2011
DOI: 10.1002/stem.614
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Activation of Bmi1 Expression Regulates Self-renewal, Apoptosis, and Differentiation of Neural Stem/Progenitor Cells In Vitro and In Vivo

Abstract: The Polycomb group protein Bmi1 is a key regulator of self-renewal of embryonic and adult central nervous system stem cells, and its overexpression has been shown to occur in several types of brain tumors. In a Cre/LoxPbased conditional transgenic mouse model, we show that fine-tuning of Bmi1 expression in embryonic neural stem cell (NSC) is sufficient to increase their proliferation and self-renewal potential both in vitro and in vivo. This is linked to downregulation of both the ink4a/ARF and the p21/Foxg1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 32 publications
3
68
1
Order By: Relevance
“…Bmi1 is a direct target gene of the Hh/Gli pathway and a putative marker of stem/progenitor cells in other organs, [24][25][26] and transient Hh activation preserved Bmi1 expression and the Bmi1 + cell population in irradiated mouse SMGs. 15 To determine whether Bmi1…”
Section: Hh-responsive Cells Do Not Directly Contribute To Regeneratementioning
confidence: 96%
“…Bmi1 is a direct target gene of the Hh/Gli pathway and a putative marker of stem/progenitor cells in other organs, [24][25][26] and transient Hh activation preserved Bmi1 expression and the Bmi1 + cell population in irradiated mouse SMGs. 15 To determine whether Bmi1…”
Section: Hh-responsive Cells Do Not Directly Contribute To Regeneratementioning
confidence: 96%
“…Subsequent to submission and decision to publish the present paper, a new study reported that Nestin-driven mild overexpression of Bmi1 enhanced the self-renewal and proliferation of apical progenitors but induced apoptosis of basal progenitors [79].…”
Section: Note In Supportmentioning
confidence: 98%
“…To explore the biological effect of enhancing Bmi1 expression in the satellite cells, we used a mouse line where Bmi1 expression can be activated in a cell-and time-specific fashion upon Cre-mediated recombination (Yadirgi et al, 2011). Transduction of satellite cell cultures derived from STOPFloxBmi1 muscles with Adeno-Cre (A-Cre) virus induced efficient recombination and increased Bmi1 expression at protein injury [d.a.i.])…”
Section: Conditional Bmi1 Expression Increases the Satellite Cell Poomentioning
confidence: 99%
“…The following transgenic lines were used: C57BL/6J-BL/10, STOPFloxBmi1 (Yadirgi et al, 2011), Bmi1 / (van der Lugt et al, 1994), R26R (Soriano, 1999), mdx (Bulfield et al, 1984), and Tg:Pax7CreER T2 (Mourikis et al, 2012). Animals were genotyped with PCR on gDNA extracted from ear notches according to standard protocols.…”
Section: Animalsmentioning
confidence: 99%